MUSIK PA’RAWANA DAN SAYYANG PATTUDDU DALAM PROSESI UPACARA KHATAM ALQURAN SUKU MANDAR DI PROVINSI SULAWESI BARAT (SEBUAH PENDEKATAN ETNOMUSIKOLOGIS) - Gunawan, Asril (Fakultas Ilmu Budaya, Universitas Mulawarman, 2017)
Pa’rawana and sayyang pattuddu music are ones of the traditional arts owned by Mandar tribe. These are very popular and always presented every year, especially at khatam Qur’an ceremony. The performance of pa’rawana and sayyang pattuddu music is always based on the socio-cultural suitability of the Mandar people who cannot be separated from their religious system. It is marked by a procession of the Qur’an recital by children. They will be paraded around the village accompanied by pa’rawana and sayyang pattuddu music. The whole process of khatam of Qur’an is very complex. In addition to the ceremonial procession, performing arts are also involved, especially pa’rawana and sayyang pattuddu music. The presentation of pa’rawana and sayyang pattuddu music is a combination of several forms of art in every performance. The incorporated arts among which consist of music pa’rawana, pa’denggo, sayyang pattuddu and pa’kalindagdag. In addition, the completeness